Citrus essential oil fractionation using ethanol with different water contents as solvents: phase equilibrium, physical properties and continuous equipment extraction - Gonçalves, Daniel (2017)
Essential oils are featured commodities in the global market due their many applications in food and chemical industries, in different medicine areas, and as antibacterial, antifungal, and antioxidant agent. One of the phenomena accountable for the loss of essential oils quality may be associated with the degradation of terpene hydrocarbons by oxidation when exposed to air, light or heat, causing disagreeable odors. The procedure of terpenes content reducing, known as deterpenation, can be performed by diverse techniques, among which the liquid-liquid extraction can be highlighted since this process can be operated without the use of heating and pressure changes, causing low impact on the essential oil sensory qualities and low energy consumption. This research was focused on the fractionation process of citrus essential oils, by liquid-liquid extraction, using ethanol/water mixtures as solvents. Experimental liquid-liquid equilibrium data of model and real citrus systems were obtained. The aroma profile of the crude citrus essential oils (orange - Citrus sinensis and lime - Citrus aurantifolia) and the phases from the liquid-liquid equilibrium was also evaluated. Moreover, the crude citrus essential oils were fractionated in a continuous operation equipment (perforated rotating disc contactor, PRDC). It was verified that the water has an important influence over the fractionation performance, but not over the aroma profile of the phases. The experimental data from the model systems (citrus essential oil model mixture + ethanol + water) were used to adjust parameters of empirical and thermodynamic models, which provided satisfactory results on the calculation of physical property values and compositions of the phases from the real systems (crude citrus essential oil + ethanol + water). The fractionation of citrus essential oils by liquid-liquid extraction technology was technically feasible and can be accomplished into continuous apparatus such as PRDC column. The solvents employed provided extract phases enriched in oxygenated compounds.